199 Pitx2c Deficiency May Increase the Antiarrhythmic Properties of Flecainide. (31st May 2014) - Syeda, Fahima; Betney, Daniel; Hopkins, Sarah; Riley, Genna; Yu, Ting; Holmes, Andrew; Brown, Nigel; Fabritz, Larissa; Kirchhof, Paulus
Abstract : Background and Objectives: Single nucleotide polymorphisms (SNPs) close to the PITX2 gene (paired-like homeodomain transcription factor 2) are associated with atrial fibrillation, including recurrent AF with therapy: Carriers of the minor allele of the most common polymorphism close to pitx2 respond well to flecainide therapy, but less well to sotalol. 1 The mechanisms underlying these clinical observations are not well understood. Heterozygous deletion of PITX2 isoform c results in reduced left atrial pitx2c mRNA expression and predisposes mice to atrial fibrillation. 2 We studied the effect of flecainide on atrial electrophysiology in PITX2c +/- mice and their wild type (WT) littermates. Methods: We studied 3–4 months old PITX2c +/- and WT mice, on an MF1 background. Hearts were rapidly excised and perfused with Krebs solution at 4ml/min, 37°C, on a modified upright Langendorff apparatus. Left atrial monophasic action potentials were recorded at baseline and during 1 µM flecainide acetate perfusion. Inter-atrial activation times (AT) and action potential durations (APD) were measured during right atrial pacing at 80–120 ms fixed-rate cycle lengths (CL). An 8-pulse S1 train, at 80–120 ms CL, followed by a single extrastimulus, S2, was delivered to measure effective refractory periods (ERP) and arrhythmia inducibility. We analysed arrhythmias, AT, ERP, APD at 70% repolarisation (APD70), and post-repolarisation refractoriness (PRR). All values are expressed as mean ± SEM. Results: Flecainide reduced atrial arrhythmias in PITX2c +/- (6/18, baseline vs 0/15, flecainide, p < 0.05) but not in WT hearts (3/15, baseline vs 3/12, flecainide). Flecainide increased AT in PITX2c +/- slightly more than WT hearts (WT 8 ± 3 ms, n = 7; PITX2c +/- 13 ± 3 ms, n.s), in a frequency-dependent manner. Flecainide did not differentially alter atrial APD (increase in APD70 at 100 ms CL; WT 0.3 ± 2, n = 8; PITX2c +/- 0.7 ± 2, n = 14). In contrast, flecainide caused a significantly greater, frequency-dependent, increase in ERP (PITX2c +/- 14 ± 2 ms, n = 13 vs WT 7 ± 2 ms, n = 10; p < 0.05) and post-repolarisation refractoriness in PITX2c +/- mice (PITX2c +/- 21 ± 3 ms, n = 6 vs WT 6 ± 4 ms, n = 6, p < 0.01). There were no mice with post repolarisation refractoriness that were susceptible to arrhythmias (0/17 mice). Conclusion: Flecainide is very effective in preventing atrial fibrillation in mice with reduced pitx2 mRNA expression. We propose that this genotype-specific antiarrhythmic effect is due to higher post-repolarisation refractoriness induced in PITX2c +/- atria. These electrophysiological data may explain why carriers of SNPs close to the PITX2 gene respond well to flecainide therapy. Funded by EU (EUTRAF) and BHF.